Classification and neuroimaging of ependymal tumors - Mu, Weiya; Dahmoush, Hisham (Frontiers in Pediatrics, 2023)
Ependymal tumors arise from ependymal rests of ventricles of the brain, central canal of the spinal cord or at the filum terminale or conus medullaris, though many pediatric supratentorial ependymomas do not demonstrate clear communication or abutment of ventricles. In this paper we discuss the classification, imaging characteristics and clinical settings of these tumors. Ependymal tumors are now classified under the 2021 WHO classification system by histopathological and molecular features, as well as location, grouped as supratentorial, posterior fossa (PF), and spinal. The supratentorial tumors are defined by either the ZFTA (formerly RELA) fusion or YAP1 fusion. Posterior fossa tumors are divided based on methylation into group A (PFA) and group B (PFB). On imaging supratentorial and infratentorial ependymomas usually abut ventricles and commonly contain calcification and cystic components, with variable hemorrhage and heterogenous enhancement. Spinal ependymomas are defined by the MYCN amplification. These tumors are less commonly calcified, and may present with the “cap sign,” T2 hypointensity due to hemosiderin deposition. Myxopapillary ependymoma and subependymoma remain tumor subtypes, with no change related to molecular classification as this does not provide additional clinical utility. Myxopapillary ependymomas are intradural, extramedullary tumors at the filum terminale and/or conus medullaris and may demonstrate the cap sign. Subependymomas are homogenous when small, and when larger can be heterogenous and contain calcification. These tumors typically do not demonstrate enhancement. Clinical presentation and prognosis vary depending on tumor location and type. Knowledge of the updated WHO CNS classification system in conjunction with imaging features is critical for accurate diagnosis and treatment.